INTERGOVERNMENTAL TAX ALLOCATION MODELS AND THEIR EFFECTIVENESS IN DEVELOPED COUNTRIES (American Journal of Business Management, Economics and Banking, 2026)
The article emphasises the significance of the inter-budget tax distribution system in state financial management and the importance of mitigating inter-regional disparities through financial, organisational, and institutional methods. Based on the experience of developed countries, it analyses models of inter-budget tax distribution and the division of powers between central and local budgets, as well as levels of financial independence.